Morphology and cytogenetics of Rhabditida nematodes parasiting spiders and Scorpions in Argentina - Camino, Nora B. (2023)
The discovery of nematodes in spiders and scorpions from a manual sampling in the city of La Plata, Argentina, revealed the presence of specimens of the order Rhabditda. The main objective of this study is to present the presence of nematodes in the arachnid group, for which there is little precedent. One of the nematodes found belongs to the genus Rhabditis Dujardin, 1845, of saprophytic character, characterized by carrying a fungus that kills the host and degrades it in order to feed itself. This was found in the general cavity of the body of the spider Dysdera crocata Koch, 1838. It is characterized by having a thin cuticle, closed labial papillae, a long stoma without teeth, an esophagus with a middle bulb with a valve and a valved basal bulb, and a middle vulva, short and conical caudal appendage. Mitotic division is described and information about the morphology of chromosomes is provided. We carried out a cytogenetic study of the Rhabditis, they showed that they have five chromosomes, of which 2 are larger, in metaphase they are acro-telocentric. The other genus found is Cruznema (Artigas, 1927) Dougherty, 1953, parasite of the intestine of the scorpion Tityus carrilloi Ojanguren-Affilastro, Kochalka, Guerrero-Orellana, Garcete-Barrett, De Roodt, Borges & Ceccarelli, 2021, characterized by having a cuticle with longitudinal striae and transverse rings, mouth surrounded by six well-separated lips, cuticularized stoma, long and with three well-developed teeth, esophagus with a strong and muscular middle bulb and a valved basal bulb, female with a prodelphic ovary, vulva posterior to the half the length of the body, caudal appendage short and conical.